Chronic exposure of Hawaii Island spinner dolphins (Stenella longirostris) to human activities. Issue 10 (24th October 2018) - Tyne, Julian A.; Christiansen, Fredrik; Heenehan, Heather L.; Johnston, David W.; Bejder, Lars
Abstract : Habitat selection is strongly influenced by spatial variations in habitat quality and predation risk. Repeated exposure of wildlife to anthropogenic activities in important habitats may affect habitat selection, leading to negative biological consequences. We quantified the cumulative human exposure of a small, genetically isolated and behaviourally constrained spinner dolphin ( Stenella longirostris ) population, off Hawaii Island, and exposure effects on their daytime cumulative activity budget. Dolphins were exposed to human activities within 100 m for 82.7% of the daytime, with a median duration of 10 min between exposure events. Individual dolphins spent on average 61.7% (s.d. = 6.5) of their daytime resting. Of their total rest time, greater than 90% occurred inside sheltered bays. Despite high levels of human exposure, we did not observe an effect on dolphin resting behaviour. The short intervals between exposure events probably prevent dolphins from returning to a natural resting state before the next event. Consequently, 'control' observations may represent a resting behaviour of a more vigilant nature. Chronic levels of exposure to human activities could lead to rest deprivation, displacement from preferred resting habitats and ultimately negative population level effects. These results have implications for new proposed legislation aiming to reduce dolphin exposure to human activities.